Code of Conduct - Buchert, Johanna (Natural Resources Institute of Finland, 2020)
In addition to the strategy, Luke’s work and activities are governed by our Code of Conduct and our values. The Code of Conduct outlines the ethical principles according to which everyone at Luke works. The Code of Conduct thus forms a foundation for all Luke’s operations and describes how we work and treat our personnel, partners and customers. As a research institute, it is extremely important to us that our work is of high quality, ambitious and reliable. Ethical standards of research, the neutrality of research and responsibility are the cornerstones of everything we do.
Keywords: proper practices; set of rules; responsibilities; norms; rules